THE INFLUENCE OF BRAND AWARENESS, BRAND AMBASSADOR, BRAND IMAGE AND BRAND TRUST ON CONSUMER PURCHASING DECISION ON THE SHOPPEE DIGITAL PLATFORM - Anggraini, Dini; Wibowo, Edwin Agung; Khuzaini, Khuzaini; Sinambela, Lasmi; Sigiro, Nia Debora (BENING, 2024)
This research aims to determine the influence of brand awareness, brand ambassador, brand image and brand trust on consumer purchasing decisions on the Shopee digital platform. This type of research is quantitative. The population in this research are Shopee service users at the Faculty of Economics and Business, Riau Islands University. The sampling technique used purposive sampling with a total sample of 86 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used in this research is classical assumption testing and multiple linear regression and hypothesis testing using the IBM SPSS V 25 application. Based on this research, it shows that brand awareness, brand image and brand trust have a positive and significant effect on purchasing decisions, while brand ambassadors have no positive and insignificant effect on purchasing decisions. And simultaneously the four variables have a positive and significant effect on purchasing decisions.